River basin closure: processes, implications and responses - Molle, Francois; Wester, P.; Hirsch, P. (Elsevier, 2010)
Increasing water withdrawals for urban, industrial, and agricultural use have profoundly altered the hydrology of many major rivers worldwide. Coupled with degradation of water quality, low flows have induced severe environmental degradation and water has been rendered unusable by downstream users. When supply of water falls short of commitments to fulfil demand in terms of water quality and quantity within the basin and at the river mouth, for part or all of the year, basins are said to be closing. Basin closure is an anthropogenic process and manifested at societal as well as ecosystem levels, and both its causes and consequences are analyzed. Implications in terms of increased interconnectedness between categories of users and between societal processes and ecosystems in different parts of river basins are emphasized. Finally, several possible responses to the challenges posed by the overexploitation of water resources are reviewed.